A COMPARATIVE ANALYSIS OF SMEAR TEST AS WOMEN’S SEXUAL HEALTH RIGHTS IN INDONESIA AND THE UNITED KINGDOM - Ratih Andani Setyo Budhi (Faculty of Law, Universitas Gadjah Mada, 2023)
Abstract Smear Test is a test that functions as a preventive measure against cervical cancer. It is important to know in advance that the process of this test will be through the cervix, so this gives rise to differences of opinion, there are several opinions that state the importance of carrying out this test because it is the initial process in detecting cervical cancer. However, there are also several countries that believe that matters related to sex and sexuality are taboo. This will further complicate efforts to protect sexual health. This article aims to examine further the views on the Smear Test which are linked to the issue of women’s sexual health rights while also examining its benefits. In the research and research process, the author will use qualitative methods and library research to obtain the necessary data. Comparative studies will also be used in comparative analysis of women’s rights to Smear Tests in the Indonesian jurisdiction compared to the UK jurisdiction and several other countries as an additional reference. Based on previous research, the author believes that Indonesia must reflect on developed countries in terms of state efforts to increase protection of the sexual health rights of its people. Overall, there are two different views from the pro and con groups regarding the implementation of the Smear Test. However, in the end the Smear Test must still be recognized by the Government as an effort to prevent its people from problems related to sexual health.Abstrak Smear Test adalah sebuah tes yang berfungsi sebagai tindakan prefentif terhadap penyakit kanker serviks. Perlu diketahui terlebih dahulu bahwa tes tersebut prosesnya akan melalui leher rahim (serviks) sehingga hal tersebut menimbulkan perbedaan pendapat, ada beberapa pendapat yang menyatakan pentingnya tes tersebut untuk dilakukan karena merupakan proses awal dalam mendeteksi penyakit kanker serviks. Meski demikian, terdapat pula beberapa negara yang percaya bahwa hal-hal yang berhubungan dengan seks maupun seksualitas merupakan suatu hal yang tabu. Hal ini akan semakin mempersulit upaya untuk melindungi kesehatan seksual. Artikel ini bertujuan untuk mengkaji lebih lanjut mengenai pandangan terhadap Smear Test yang dikaitkan dengan isu hak kesehatan seksual perempuan sekaligus juga mengkaji manfaatnya. Dalam proses riset dan penelitian, Penulis akan menggunakan metode kualitatif serta penelitian kepustakaan untuk memperoleh data yang diperlukan. Studi komparatif juga akan digunakan dalam menganalisis perbandingan atas hak perempuan terhadap Smear Test dalam yurisdiksi Indonesia dibandingkan dengan yurisdiksi Inggris serta beberapa negara lainnya sebagai referensi tambahan. Berdasarkan penelitian yang ada sebelumnya, Penulis berpendapat bahwa Indonesia wajib berkaca pada negara-negara maju dalam hal upaya negara untuk meningkatkan perlindungan terhadap hak kesehatan seksual masyarakatnya. Secara keseluruhan, terdapat dua pandangan yang berbeda dari kelompok pro maupun kontra mengenai implementasi Smear Test ini. Namun, pada akhirnya Smear Test tetap harus diakui oleh Pemerintah sebagai upaya untuk menghindari masyarakatnya dari permasalahan-permasalahan yang berkaitan dengan kesehatan seksual.